2000
DOI: 10.1021/np000292h
|View full text |Cite
|
Sign up to set email alerts
|

Activity-Guided Isolation of Antioxidative Constituents ofCotinuscoggygria

Abstract: Six constituents (1-6) were isolated from EtOAc-soluble partitions of two separate collections of the whole plants of Cotinus coggygria, namely, disulfuretin ¿2,2'-[1,2-bis(3,4-dihydroxyphenyl)-1, 2-ethanedylidene]bis[6-hydroxy-3(2H)-benzofuranone] (1)¿, sulfuretin (2), sulfurein (3), gallic acid (4), methyl gallate (5), and pentagalloyl glucose (6). The structure of the novel biaurone 1 was determined by spectral and chemical methods. Compounds 1-6 were found to be potent antioxidants in a 1,1-diphenyl-2-picr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
57
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(62 citation statements)
references
References 21 publications
2
57
0
Order By: Relevance
“…Of these, methyl gallate has been demonstrated to possess antioxidant activity and to inhibit lipid peroxidation (Wu et al 1998;Mei et al 1999;Westenburg et al 2000;Galato et al 2001). Hsieh et al (2004) demonstrated that methyl gallate extracted from TSR could suppress H 2 O 2 -mediated oxidative stress and DNA damage via scavenging of intracellular reactive oxygen species, inhibiting lipid peroxidation and preventing the depletion of intracellular glutathione level in Madin -Darby canine kidney cells (Hsieh et al 2004).…”
Section: ·75 £ 10mentioning
confidence: 99%
“…Of these, methyl gallate has been demonstrated to possess antioxidant activity and to inhibit lipid peroxidation (Wu et al 1998;Mei et al 1999;Westenburg et al 2000;Galato et al 2001). Hsieh et al (2004) demonstrated that methyl gallate extracted from TSR could suppress H 2 O 2 -mediated oxidative stress and DNA damage via scavenging of intracellular reactive oxygen species, inhibiting lipid peroxidation and preventing the depletion of intracellular glutathione level in Madin -Darby canine kidney cells (Hsieh et al 2004).…”
Section: ·75 £ 10mentioning
confidence: 99%
“…The persistent production of abnormally large amount of ROS or RNS, however, Methyl gallate and chemicals structurally related to methyl gallate protect human umbilical vein endothelial cells from oxidative stress may lead to persistent changes in signal transduction and gene expression, which in turn may give rise to certain diseases. meGAL is known as one of major antioxidants (Westenburg et al, 2000;Galato et al, 2001;Cho et al, 2003;Sohi et al, 2003). meGAL is a phytochemical from various species including Meliaceae, Rosa Rugosa and Galla Rhois, and its derivative (-)-epigallocatechin gallate (EGCG) is a major pytochemical of green tea, well known antioxidative beverage (Chen and Zhang, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…meGAL is a phytochemical from various species including Meliaceae, Rosa Rugosa and Galla Rhois, and its derivative (-)-epigallocatechin gallate (EGCG) is a major pytochemical of green tea, well known antioxidative beverage (Chen and Zhang, 2003). The radical scavenging effect and inhibition of LPO have been reported as major activities of meGAL (Westenburg et al, 2000;Galato et al, 2001;Cho et al, 2003). In addition, meGAL possesses the biological activities including antiplatelet activity (Lim et al, 2004), protection of DNA damaging against oxidative stress (Hsieh et al, 2004), protection of lung injury induced by phosgene (Sciuto and Moran, 2001), attenuation of diabetic oxidative stress (Cho et al, 2004) and antiapoptotic activity (Sohi et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Gallicin is reported to have antioxidant [47], antitumor [48] antiplatelet [49], antimicrobial [50], anti-inflammatory and cyclooxygenase-2/5-lipoxygenase inhibitory [51] activity. Gallic acid has been shown to have antioxidant [52,53], anti-inflammatory, cytotoxic and bactericidal activity [53], gastric protective action [53] and antiangiogenic activity [54]. -Sitosterol is reported to show antioxidant [55], anti-inflammatory [56], analgesic and anthelmintic [57] activity.…”
mentioning
confidence: 99%